Penerimaan Teknologi QRIS bagi Pelaku UMKM Kabupaten Banyumas Menggunakan Technology Acceptance Model (TAM) - Saputra, Jeffri Prayitno Bangkit; Waluyo, Retno; Lestari, Dwi Puji; Ramadhani, Sekar Ajeng (Universitas Merdeka Malang, 2024)
The growth of MSMEs in Banyumashas experienced rapid development. Some MSME actors in the region have utilized QRIS as an online transaction tool, which offers various advantages. However, the implementation of QRIS still faces several obstacles, such as limited network infrastructure,as well as social and cultural aspects related to the acceptance and adaptation of technology in society. This study aims to analyze the factors influencing the acceptance of QRIS usage by MSME actors in Banyumas using the Technology Acceptance Model (TAM). The external variables analyzed include information quality, system quality, and computer self-efficacy. The sample size used was 150 respondents. The research results show that the factors of information quality and computer self-efficacy do not impactperceived usefulness. Conversely, all the external factors analyzed have a significant impact on perceived ease of use. Additionally, the research findings reveal that perceived usefulness does not influence behavioral intention, whereas perceived ease ofuse affects behavioral intention. Furthermore, the factor of behavioral intention has a positive impact on actual system use of QRIS technology among MSME actors in Banyumas.